B cell-regulated immune responses in tumor models and cancer patients - Fremd, Carlo; Schütz, Florian; Sohn, Christof; Beckhove, Philipp; Domschke, Christoph (OncoImmunology, 2013)
The essential role played by T cells in anticancer immunity is widely accepted. The immunosuppressive functions of regulatory T cells are central for tumor progression and have been endowed with a robust predictive value. Increasing evidence indicates that also B cells have a crucial part in the regulation of T-cell responses against tumors. Although experiments reporting the production of natural antitumor antibodies and the induction of cytotoxic immune responses have revealed a tumor-protective function for B cells, other findings suggest that B cells may also exert tumor-promoting functions, resulting in a controversial picture. Here, we review recent evidence on the interactions between B and T cells in murine models and cancer patients and their implications for cancer immunology.